1985
DOI: 10.2307/3429881
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Human Studies on Polychlorinated Biphenyls (PCBs) and Related Compounds

Abstract: Similar qualitative toxic effects have been observed in animals for a class of halogenated aromatic compounds, which include the halogenated biphenyls, naphthalenes, dibenzodioxins, and dibenzofurans. All of these compounds are lipid soluble and persist in the environment and in mammals. The polybrominated biphenyls (PBBs) are the most persistent. They are predominantly stored in fatty tissue; they pass the placenta and are excreted in milk. Some isomers of the halogenated biphenyls are more toxic than others.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…PCBs were manufactured for many purposes, including insulators, fire retardants, lubricants for heavy machinery and dielectric fluid in transformers. With long environmental half-lives (Kimbrough 1985), these POPs will remain in the environment for decades to come.…”
Section: Introductionmentioning
confidence: 99%
“…PCBs were manufactured for many purposes, including insulators, fire retardants, lubricants for heavy machinery and dielectric fluid in transformers. With long environmental half-lives (Kimbrough 1985), these POPs will remain in the environment for decades to come.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to PCBs is associated with a broad spectrum of human health problems, including neurotoxicity, hepatotoxicity, hypothyroidism, and immunodeficiency (1,3,(6)(7)(8).…”
mentioning
confidence: 99%
“…Commercial production of these compounds was banned in 1979; however, PCBs continue to be a health concern due to their persistence in the environment and demonstrated toxic effects. Numerous toxicity studies have been carried out on commercial PCBs and have demonstrated a broad range of toxic effects (Kimbrough, 1985;Safe, 1994). Recent advances in analytical chemistry have shown that not all congeners of PCBs are retained in biological systems (Duinker & Hillebrand, 1983;Williams & LeBel, 1990;Mes et al, 1993).…”
mentioning
confidence: 99%
“…Polychlorinated biphenyl (PCBs) have been widely used since the 1930s as ingredients for dielectric fluids and lubricants (Kimbrough, 1985;Jensen, 1966). Commercial production of these compounds was banned in 1979; however, PCBs continue to be a health concern due to their persistence in the environment and demonstrated toxic effects.…”
mentioning
confidence: 99%